Aspects of social organization in anuran choruses - Bishop, Phillip John (My University, 2016)
species of anurens , By utilizing acoustio playbaok " "." :1.. (1 ',' .., experiments the exact' rlature it! call timing' in, five species was determined.' ~t)'U): specie~, each exl1ibi ted one "of three" distinot:: types Qf chozus organizatioh, while in one sp~ci.es it. was not possible to demonstrQ.te any chorus organization. The distinct: t.ype Qf ("chorus organizatidh that a species • c;. -" < . " ,', '. ~hib:l t;s . was shown to be a function of '"call duration and 0 behavioural refractory period. Go' . c' .~ The Significance of oall intensity in male~male '.\. interactions and female mate choice was determined in fU:t;"ther acoust,i21 ~layback experiments. ':Males"exhibited a. g.t,-,d",ed·type of'" r.esponSe, with the perc~ntage of ,.'aggresSive ;:, . caitn~,\~pc:r:easi'1l9with increasing intensity?f the playback. 11 Althou~tf females wer~ unable to compute absoltl,te intensity / ' they We,'~.1{:;l pr~fer~ntiall.Y attracted to thE! louder of two calls in simple" two-choice sitl,:lations, but their q,isc;riJninatory ability was impaired" in more complex situations ..Males of H. marmoratus. were ;found to call at ;f:~~~ c; coflsi:stentl.y different tepetit~on rates and :females l) preferE:mtiall,y selected :faster r~tes in simple two.;ochoice I;> experiments aSq~ell as in +,.1;ief;i.eld .. This study prqvides va~uable~' insigllt into t'~ " ' dynainios of several species, E.f;!.ab.l4J)'ij<' '8 understanding of the 'function· and signif Lcance ubiquitou~ phenomenon of chorus organi.zation.
Thesis submitted to th~ Faculty of Scien9,~1 University of the Witwate:esrandJ JOham1esburg I' - 0 in fuJ,filmep:c of the reqtt!,'lernents for the degree .of DoCtor of .Philo~ ~phy JOHANNESBURG C/ o (~J July 1994
Keywords: Amphibians--behaviour; Anura